Electroluminescence from Serpentine Carbon Nanotube Based Light‐Emitting Diodes on Quartz. Issue 6 (8th November 2013) - Yu, Dangmin; Wang, Sheng; Ye, Linhui; Li, Wei; Zhang, Zhiyong; Chen, Yabin; Zhang, Jin; Peng, Lian‐Mao
<x xml:space="preserve">Abstract</x> A light‐emitting diode is fabricated and characterized on a semiconducting serpentine CNT which has many parallel segments with identical chirality. Compared with the individual CNT and CNT‐film devices, the device with parallel segments shows improvement of an order of magnitude in current, significantly larger electroluminescent intensity, and narrower emission bands. Serpentine nanotubes are an ideal choice for practical applications of CNT‐based light sources. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>